Unexpected and durable response with regorafenib in a metastatic colorectal cancer patient without KDR mutation: A case report. Issue 25 (June 2018) - Rosati, Gerardo; Del Gaudio, Nunzio; Scarano, Enrico; Cifarelli, Rosa Anna; Altucci, Lucia; Bilancia, Domenico
Abstract: Rationale: Regorafenib is an oral multikinase inhibitor and is approved as salvage therapy in the standard treatment of advanced colorectal cancer (CRC). Due to its limited efficacy, toxicity profile, and cost, it is necessary to identify those patients who may have the most benefit from regorafenib. In a previous case report, kinase insert domain receptor ( KDR ) mutation has been associated with exceptional clinical response (CR) in an elderly patient treated with a low dose of regorafenib; thus, it was hypothesized that it could represent a new predictive marker of drug response. Patient concerns: A heavily pretreated 67-year-old man with a wide peripancreatic recurrence of colon carcinoma and liver metastases was subjected to treatment with regorafenib. Diagnoses: After 3 months of therapy, a computed tomography scan showed an impressive reduction of disease. Interventions: Regorafenib was given at full doses (160 mg/die for 21 days, every 4 weeks). Outcomes: A lasting response without relevant toxicity. No KDR mutation relief was detected. After 13 months from the start of treatment, the patient died after the diagnosis of encephalic metastases. Lessons: Regorafenib can lead to an unexpected and durable CR with consistent progression-free survival and overall survival benefit even in patients affected by polychemotherapy refractory metastatic CRC. Further studies are needed to establish the benefit of KDR mutation as predictive marker for regorafenib sensitivity for patients with CRC. We include a detailed revision of prognostic and predictive factors of clinical outcome identified in literature to optimize the use of regorafenib in this setting.